Jetpack Compose 1. 6 Essentials: Developing Android Apps with Jetpack Compose 1. 6, Android Studio, and Kotlin - Smyth, Neil (Payload Media, 2024)
Jetpack Compose 1.6 Essentials is a comprehensive guide that teaches you how to create Android applications using Jetpack Compose 1.6, Android Studio, Material Design 3, and the Kotlin programming language, with detailed tutorials included throughout the book to help you put theory into practice.